Twisted olefinic building blocks for low bandgap polymers in solar cells and ambipolar field‐effect transistors. Issue 7 (28th October 2015) - Chiu, Chien‐Yang; Wang, Hengbin; Phan, Hung; Shiratori, Kazuya; Nguyen, Thuc‐Quyen; Hawker, Craig J.
ABSTRACT: A series of polymers based on 8, 8′‐biindeno[2, 1‐b]thiophenylidene for use in photovoltaic devices and field‐effect transistors are reported. These structurally twisted olefins are effective building blocks for preparation of low bandgap polymers with optical bandgaps of 1.2–1.5 eV. Device performance, such as V oc and J sc, in solar cell devices could be successfully modulated by incorporation of a variety of comonomers. Ambipolar properties in field‐effect transistors using Au electrodes were also studied, withP t BTPDPP exhibiting balanced charge transport properties with hole and electron mobilities of 0.09 and 0.12 cm 2 ·V −1 ·s −1, respectively. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 889–899 Abstract : A series of conjugated polymers based on structurally twisted building blocks are reported. These 8, 8′‐biindeno[2, 1‐b]thiophenylidene‐based polymers exhibit low bandgap properties and lead to good performances in solar cells and ambipolar field‐effect transistors.